(untitled) (Medico Legal Update, 2021)
Breast cancer is one of the most deadly cancers threatening life and is the most prevalent among women worldwide and in general is the second most common type of cancer. The aim of this study was to identify the expression of microRNAs and biomarkers for early detection of breast cancer. MicroRNAs have become a hot subject in cancer research today because of their important role not only in cancer progression, progression, But also suppress genes related to cancer. With advanced techniques, these microRNAs can be easily detected from biopsy samples and blood for early diagnosis, diagnosis and treatment. Due to the increase in the demand for research in the exploration of the microRNAs profile in relation to different subtypes of breast cancer, the role of microRNA microRNA as an oncomir or oncosupressor, and discovery of microRNAs and miRNAs potentials for the treatment of breast cancer. MiR is involved in a variety of natural physiological processes, specifically identifying and identifying cell type. It has become clear that they are also major factors in cancer. Here we discuss what is known about miR biology in natural breast, and the emerging roles in breast cancer.